2023
DOI: 10.3389/fpubh.2023.1125150
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Physio-metabolic and clinical consequences of wearing face masks—Systematic review with meta-analysis and comprehensive evaluation

Abstract: BackgroundAs face masks became mandatory in most countries during the COVID-19 pandemic, adverse effects require substantiated investigation.MethodsA systematic review of 2,168 studies on adverse medical mask effects yielded 54 publications for synthesis and 37 studies for meta-analysis (on n = 8,641, m = 2,482, f = 6,159, age = 34.8 ± 12.5). The median trial duration was only 18 min (IQR = 50) for our comprehensive evaluation of mask induced physio-metabolic and clinical outcomes.ResultsWe found significant e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 188 publications
0
9
0
Order By: Relevance
“…An exposure to a mixture of VOC as shown for face masks according to our results (TVOC, Table 2) [24,25,56,71,72] may be an important trigger of the so-called Sick Building Syndrome (SBS) [155]. SBS-like symptoms have been linked to mask use in recent comprehensive reviews on adverse face mask effects [26,62,63]. Possibly, some of the symptoms immediately occurring while wearing a mask may be caused by toxic chemicals released by the face mask.…”
Section: Vocs -Risksmentioning
confidence: 78%
See 3 more Smart Citations
“…An exposure to a mixture of VOC as shown for face masks according to our results (TVOC, Table 2) [24,25,56,71,72] may be an important trigger of the so-called Sick Building Syndrome (SBS) [155]. SBS-like symptoms have been linked to mask use in recent comprehensive reviews on adverse face mask effects [26,62,63]. Possibly, some of the symptoms immediately occurring while wearing a mask may be caused by toxic chemicals released by the face mask.…”
Section: Vocs -Risksmentioning
confidence: 78%
“…Of the original 1003 results, 24 studies (2.4%) were finally included (Figure 1). This is not an unusually low rate in reviews [62,63]. Moreover, our selection was strictly based on the inclusion and exclusion criteria and the quality assessment applied.…”
Section: General Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been shown to cause elevated transcutaneous carbon dioxide values and lower oxygen availability [45,51], which can lead to short-term confusion, disorientation, impaired cognitive abilities, and drowsiness, symptoms that have been collectively referred to as maskinduced exhaustion syndrome (MIES) by Kisielinski et al [45]. More recently, Kisielinski et al reported a systematic review with meta-analysis demonstrating that masks interfere with O 2 -uptake and CO 2 -release and providing evidence that masks lead to adverse physio-metabolic and clinical outcomes, thereby validating MIES, especially for vulnerable groups, such as children, pregnant women, the elderly, and people suffering from illnesses [52]. With regards to issues of CO 2 release, it has been reported that mask wearing rapidly leads to children inhaling CO 2 at concentrations above the accepted safe levels [53], the long term implications of which to children's health are unknown.…”
Section: Physical Harmsmentioning
confidence: 99%